![\large \boxed{(f + g)(x) = f(x) + g(x)}](https://tex.z-dn.net/?f=%20%5Clarge%20%20%5Cboxed%7B%28f%20%2B%20g%29%28x%29%20%3D%20f%28x%29%20%2B%20g%28x%29%7D)
The property above is distribution property where we distribute x-term in the function.
Substitute both f(x) and g(x) in.
![\large{ \begin{cases} f(x) = 2 {x}^{2} - x - 6 \\ g(x) = 4 - x \end{cases}} \\ \large{f(x) + g(x) = (2 {x}^{2} - x - 6) + (4 - x)} \\ \large{f(x) + g(x) = 2 {x}^{2} - x - 6 + 4 - x}](https://tex.z-dn.net/?f=%20%5Clarge%7B%20%5Cbegin%7Bcases%7D%20f%28x%29%20%3D%202%20%7Bx%7D%5E%7B2%7D%20%20%20-%20%20x%20-%206%20%5C%5C%20g%28x%29%20%3D%20%204%20-%20x%20%5Cend%7Bcases%7D%7D%20%20%5C%5C%20%20%5Clarge%7Bf%28x%29%20%2B%20g%28x%29%20%3D%20%282%20%7Bx%7D%5E%7B2%7D%20%20-%20x%20-%206%29%20%2B%20%284%20-%20x%29%7D%20%5C%5C%20%20%5Clarge%7Bf%28x%29%20%2B%20g%28x%29%20%3D%202%20%7Bx%7D%5E%7B2%7D%20%20-%20x%20-%206%20%2B%204%20-%20x%7D)
Évaluate/Combine like terms.
![\large{f(x) + g(x) = 2 {x}^{2} - 2x - 2}](https://tex.z-dn.net/?f=%20%5Clarge%7Bf%28x%29%20%20%2B%20g%28x%29%20%3D%202%20%7Bx%7D%5E%7B2%7D%20%20-%202x%20-%202%7D%20)
The function can be factored so there are two answers. (Both of them work as one of them is factored form while the other one is not.)
![\large{(f + g)(x) = 2 {x}^{2} -2x -2}](https://tex.z-dn.net/?f=%20%5Clarge%7B%28f%20%2B%20g%29%28x%29%20%3D%202%20%7Bx%7D%5E%7B2%7D%20%20-2x%20-2%7D)
<u>Alternative</u>
![\large{(f + g)(x) = 2({x}^{2} -x - 1)}](https://tex.z-dn.net/?f=%20%5Clarge%7B%28f%20%2B%20g%29%28x%29%20%3D%202%28%7Bx%7D%5E%7B2%7D%20%20-x%20-%201%29%7D)
<u>Answer</u>
- (f+g)(x) = 2x²-2x-2
- (f+g)(x) = 2(x²-x-1)
Both answers work. The second answer is in factored form.
Let me know if you have any doubts!
Answer:
a+9b+10
Step-by-step explanation:
use foil method
Answer:
5
Step-by-step explanation:
-1+(1)= 0
0+(4)=4
1+4=5
750+20(30)=1350
Or do you need to explain it?